Optimality and Duality for Multiobjective Fractional Programming Involving Nonsmooth Generalized (ℱ, b, ϕ, ρ, θ)-Univex Functions. (20th November 2013) - Liu, Jen-Chwan; Liu, Chun-Yu
Abstract : We establish properly efficient necessary and sufficient optimality conditions for multiobjective fractional programming involving nonsmooth generalized ( ℱ, b, ϕ, ρ, θ ) -univex functions. Utilizing the necessary optimality conditions, we formulate the parametric dual model and establish some duality results in the framework of generalized ( ℱ, b, ϕ, ρ, θ ) -univex functions.